Dampak Pandemi Covid-19 Terhadap Pendapatan Para Pedagang Kuliner di Kawasan Wisata PantaiGandoriah Di Kota Pariaman - sari, marni novita (Studi Budaya Nusantara, 2021)
Gandoriah Beach in Pariaman City has become a culinary trade centre. However, since the outbreak of the Covid-19 pandemic, there has been a decline in the community's economy, especially for culinary traders. The research problem is how the COVID-19 pandemic has affected the income of food vendors and what strategies they have employed to overcome economic challenges. The objective of this study is to identify the impacts felt by food vendors so that they can address economic issues and sustain their operations to date. The research method employed is a qualitative approach with a descriptive research design. The COVID-19 pandemic has impacted the income of vendors in the Gandoriah Beach tourist area of Pariaman City, resulting in a decrease in income. This includes a decline in family income and a reduction in sales received. Additionally, there have been adjustments to the rules governing their operations. In response, vendors have developed strategies to mitigate the pandemic's impact, enabling them to continue operating.